Magnetic extraction of toxin binding liposomes; a method to ameliorate drug toxicity? Preliminary in vitro/in vivo study. (20th November 2018) - Cave, Grant; Harvey, Martyn; Sleigh, Jamie; Kanamala, Manju; Wu, Zimei
Aim: Removal of a toxin from the body once absorbed is usually not possible. We describe the use of magnetite containing pH gradient 'MagnepH' liposomes to overcome limitations preventing removal.Methods: MagnepH liposomes were added to albumin solution containing amitriptyline and dosed intravenously in rats prior to amitriptyline injection. Albumin solution or drawn blood was exposed to a magnet and sampled.Results: One third of amitriptyline was extracted in vitro . In vivo amitriptyline concentrations were 1830 nmol/l (controls) and 10870 nmol/l (MagnepH; n = 2). Amitriptyline extraction increased from 0.6% (control) to 10.4% (MagnepH; 95% CI for difference 2.0–17.6%).Conclusion: MagnepH liposomes sequestered amitriptyline and could then be extracted. This method has potential to ameliorate limitations to extracorporeal removal of toxins in poisoning.